Why Conservation Matters and What We Can Do About It - Sawhill, John (Maine Policy Review, 1995)
While environmental and economic needs have long been considered to be in direct opposition to one another, a new approach to environmental conservation is emerging. Called the "ecosystem" approach, it focuses not only on protecting the environment and its species, but also seeks new ways of balancing these interests with human needs. The article is drawn from a speech delivered by John C. Sawhill at the Summer Lecture Series of the College of the Atlantic,Bar Harbor,Maine, on August 2, 1994. Sawhill outlines the conservation principles that guide The Nature Conservancy and provides examples of how the ecosystem approach has led to successful outcomes for both people and the environment.